Characterization of the complete chloroplast genome of Gentiana rhodantha (Gentianaceae). Issue 1 (2nd January 2020) - Ling, Li-Zhen
Abstract: The first complete chloroplast genome (cp) sequences of Gentiana rhodantha were reported in this study. The cp genome of G. rhodantha was 148, 967 bp in size, with two inverted repeat (IR) regions of 25, 760 bp, the large single copy (LSC) region of 79, 831 bp, and the small single copy (SSC) region of 17, 616 bp. The cp genome contained 112 genes, including 78 protein-coding genes, 4 ribosomal RNA, and 30 transfer RNA genes. The overall GC content was 36.4%. Phylogenetic analysis of the cp genomes within the tribe Gentianeae suggests that G. rhodantha is in a sister clade of other subtribe Gentianinae.